Asia's cultural mosaic : (Prentice Hall, 1999)
This book is for students of Asia. It takes mainsteam anthropological thems on kinship, the economy or gender and examines them through the available empirical material on Asian cultures and societies provided by anthropologists, sociologists and others. It ranges from India to Japan, from Mongolia to Indonesia; and despite the fact that some places and some specific topics are treated in greater depth than others, anyone who reads this book from cover to cover will learn a lot about the cultures of Asia.